2018
DOI: 10.1001/jamapsychiatry.2018.0335
|View full text |Cite
|
Sign up to set email alerts
|

Association of Cannabis With Cognitive Functioning in Adolescents and Young Adults

Abstract: Associations between cannabis use and cognitive functioning in cross-sectional studies of adolescents and young adults are small and may be of questionable clinical importance for most individuals. Furthermore, abstinence of longer than 72 hours diminishes cognitive deficits associated with cannabis use. Although other outcomes (eg, psychosis) were not examined in the included studies, results indicate that previous studies of cannabis in youth may have overstated the magnitude and persistence of cognitive def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
253
4
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 303 publications
(290 citation statements)
references
References 136 publications
20
253
4
3
Order By: Relevance
“…A review on cognitive dysfunctions in patients with cannabis dependence showed impairments in executive functions, even after a period of abstinence . Nonetheless, with time, the magnitude of the effect size on executive function would reduce substantially . The estimated effect size (0.17‐0.21) in our study was comparable to the published literature.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…A review on cognitive dysfunctions in patients with cannabis dependence showed impairments in executive functions, even after a period of abstinence . Nonetheless, with time, the magnitude of the effect size on executive function would reduce substantially . The estimated effect size (0.17‐0.21) in our study was comparable to the published literature.…”
Section: Discussionsupporting
confidence: 72%
“…We studied a wide range of cognitive functions: decision making, cognitive impulsivity, cognitive flexibility, conceptual thinking, attention, and working memory. We have accounted for some of the potential confounders and effect modifiers such as years of education, age of the participants, the severity of opioid dependence, and presence of co‐morbidities . The GLM controlled for the effect of the group difference in the mean age of the participants and the mean years of education.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in a recent meta-analysis [13], it could be demonstrated that in most studies in youth the magnitude and persistence of cognitive deficits of cannabis have been overstated. In the authors’ opinion, reported deficits reflect residual effects from acute use or withdrawal rather than persistent cognitive deficits.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Recent high‐profile meta‐analyses have reported that adolescent cannabis use is not a major risk factor for a number of previously linked mental health problems (e.g. ). For example, Gobbi and colleagues recently reported in a meta‐analysis of longitudinal studies that adolescent cannabis use was not significantly related to anxiety in young adulthood, and modestly related to depression .…”
Section: Summary Of Adolescent Cannabis Use Measurement Years For Lonmentioning
confidence: 99%